Respiratory symptoms among infants at risk for asthma: association with surfactant protein A haplotypes - Bracken Michael B; Holford Theodore R; Belanger Kathleen D; Triche Elizabeth W; Zhu Yong; Gent Janneane F; Pettigrew Melinda M; Leaderer Brian P (BMC, 2007)
Abstract Background We examined the association between single nucleotide polymorphisms (SNPs) in loci encoding surfactant protein A (SFTPA) and risk of wheeze and persistent cough during the first year of life among a cohort of infants at risk for developing asthma. Methods Between September 1996 and December 1998, mothers of newborn infants were invited to participate if they had an older child with clinician-diagnosed asthma. Each mother was given a standardized questionnaire within 4 months of her infant's birth. Infant respiratory symptoms were collected during quarterly telephone interviews at 6, 9 and 12 months of age. Due to the association of SFTPA polymorphisms and race/ethnicity, analyses were restricted to 221 white infants for whom whole blood and respiratory data were available. Ordered logistic regression models were used to examine the association between respiratory symptom frequency and SFTPA haplotypes. Results The 6A allele haplotype of SFTPA1, with an estimated frequency of 6% among our study infants, was associated with an increased risk of persistent cough (OR 3.69, 95% CI 1.71, 7.98) and wheeze (OR 4.72, 95% CI 2.20, 10.11). The 6A/1A haplotype of SFTPA, found among approximately 5% of the infants, was associated with an increased risk of persistent cough (OR 3.20, 95% CI 1.39, 7.36) and wheeze (OR 3.25, 95% CI 1.43, 7.37). Conclusion Polymorphisms within SFTPA loci may be associated with wheeze and persistent cough in white infants at risk for asthma. These associations require replication and exploration in other ethnic/racial groups.